Negotiate Without Fear - Medvec, Victoria (Ascent Audio, 2021)
With Negotiate Without Fear: Strategies and Tools to Maximize Your Outcomes, master negotiator, Kellogg professor, and accomplished CEO Victoria Medvec delivers an authoritative and practical resource for eliminating the fear that impedes success in negotiation. In this book, listeners will discover unique and proprietary negotiation strategies honed over decades advising Fortune 500 clients on high-stakes, complex negotiations. Negotiate Without Fear provides listeners at all levels of negotiation skill the ability to increase their negotiating confidence and maximize their negotiation success. You'll learn how to: put the right issues on the table by defining your objectives for the negotiation; analyze the issues being negotiated with an Issue Matrix to ensure you have the right issues to secure what you want; establish ambitious goals using a proprietary tool to identify the weaknesses in the other side's best outside alternative (BATNA); and leverage a unique architecture for creating and delivering Multiple Equivalent Simultaneous Offers (MESOs). Additionally, specific advice is provided in every chapter for individuals who are negotiating for themselves and in the everyday world. This book is an invaluable guide for anyone who hopes to sharpen their negotiating skills and achieve success in any arena.